“Linguistic turn” in Humanitarian Studies: XIII Congress of Anthropologists and Ethnologists of Russia - A. A. Boronin (Научный диалог)
The linguistic component of the materials of the XIII Congress of Anthropologists and Ethnologists of Russia (Kazan, July 2-6, 2019) is discussed in the article. It is concluded that the research approaches of anthropologists, ethnologists and linguists coming close, interpreted as a potential starting point for the increment of new linguistic knowledge.